Residual venous obstruction in patients with a single episode of deep vein thrombosis and in patients with recurrent deep vein thrombosis - Galli, Matteo; Ageno, Walter; Squizzato, Alessandro; Dentali, Francesco; Manfredi, Elisa; Steidl, Luigi; Venco, Achille (Thrombosis and Haemostasis, 2005)
Residual venous obstruction (RVO) in patients with previous deep vein thrombosis (DVT) of the lower limbs has been suggested as an independent risk factor for recurrent venous thromboembolism (VTE).RVO could be a marker of a persistent prothrombotic state. We have compared the rate of RVO in patients with DVT and a personal history of at least one previous episode of VTE to the rate of RVO among patients with a first episode of DVT. All patients underwent compression ultrasonography (CUS) of the lower limbs 1 year after index DVT. RVO was arbitrarily defined as a thrombus occupying, at maximal compressibility, more than 20% of the vein area in the absence of compression. 50 consecutive patients with recurrent DVT and 50 age and sex-matched patients with a single episode of DVT were enrolled. The index event was idiopathic in 62% of patients with recurrent DVT and in 60% of patients with a single episode. In 74% of patients with recurrent DVT the index event occurred in either the contralateral leg or in a different segment of the ipsilateral leg. RVO was detected in 50% of patients with a single episode of DVT and in 88% of patients with recurrent DVT (p<0.00001). The prevalence of RVO is significantly higher in patients with recurrent DVT than in patients with a single episode. This finding supports the importance of RVO as a potential marker of a persistent prothrombotic state.
Keywords: Deep vein thrombosis; recurrence; residual venous obstruction